2021
DOI: 10.48550/arxiv.2111.00065
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

X-ray Simulations of Polar Gas in Accreting Supermassive Black Holes

Jeffrey McKaig,
Claudio Ricci,
Stéphane Paltani
et al.

Abstract: Recent observations have shown that a large portion of the mid-infrared (MIR) spectrum of active galactic nuclei (AGN) stems from the polar regions. In this paper, we investigate the effects of this polar gas on the X-ray spectrum of AGN using ray-tracing simulations. Two geometries for the polar gas are considered, (1) a hollow cone corresponding to the best fit MIR model and (2) a filled cone, both with varying column densities (ranging from 10 21 − 10 22.5 cm −2 ) along with a torus surrounding the central … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 58 publications
(92 reference statements)
0
2
0
Order By: Relevance
“…For example, Mn K𝛼 at 5.88 keV was identified as Cr XXIV in Arévalo et al (2014) using MYT , while it is naturally produced by our model. The accretion disk and the BLR can strongly affect the reprocessed continuum emission and the Fe K𝛼 complex, while the polar component is expected to contribute significantly to the AGN emission at 𝐸 5 keV McKaig et al (2021), enhancing the flux of some of the emission lines (e.g., Liu et al 2019;McKaig et al 2021).…”
Section: S17 S19mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Mn K𝛼 at 5.88 keV was identified as Cr XXIV in Arévalo et al (2014) using MYT , while it is naturally produced by our model. The accretion disk and the BLR can strongly affect the reprocessed continuum emission and the Fe K𝛼 complex, while the polar component is expected to contribute significantly to the AGN emission at 𝐸 5 keV McKaig et al (2021), enhancing the flux of some of the emission lines (e.g., Liu et al 2019;McKaig et al 2021).…”
Section: S17 S19mentioning
confidence: 99%
“…This emission could be related, at least in some cases, to the polar dust observed in the MIR (e.g., Liu et al 2019). It has been also suggested that the polar component might be responsible for some of the narrow emission features observed at 𝐸 3 keV in heavily obscured AGN, such as the Si K𝛼 line (e.g., Liu et al 2019;McKaig et al 2021).…”
Section: Introductionmentioning
confidence: 96%